2021
DOI: 10.1145/3460823
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors Affecting User Adoption of Open-Access Data Repositories in Intelligence and Security Informatics: An Affordance Perspective

Abstract: Rich, diverse cybersecurity data are critical for efforts by the intelligence and security informatics (ISI) community. Although open-access data repositories (OADRs) provide tremendous benefits for ISI researchers and practitioners, determinants of their adoption remain understudied. Drawing on affordance theory and extant ISI literature, this study proposes a factor model to explain how the essential and unique affordances of an OADR (i.e., relevance, accessibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Through structural equation modelling, they revealed that affordance derived from the mobile app significantly impacts the perceived value. Albeit in a different context, similar results can also be found in the study by Wen et al [52], where there is a significant relationship between the affordances of open-access data repositories and perceived value. They assessed this relationship through PLS-SEM, due to the suitability of the method, to test a model that contains both formative and reflective constructs.…”
Section: Perceived Ecotourism Design Affordances and Perceived Value ...supporting
confidence: 85%
See 2 more Smart Citations
“…Through structural equation modelling, they revealed that affordance derived from the mobile app significantly impacts the perceived value. Albeit in a different context, similar results can also be found in the study by Wen et al [52], where there is a significant relationship between the affordances of open-access data repositories and perceived value. They assessed this relationship through PLS-SEM, due to the suitability of the method, to test a model that contains both formative and reflective constructs.…”
Section: Perceived Ecotourism Design Affordances and Perceived Value ...supporting
confidence: 85%
“…For this reason, the matching perceptions of the values generated from the uptake of the product by the tourist can lead to significant interaction with the tourism managers, while reducing the possibilities of diminishing values (see [51]). Conceivably, individuals will be steered away from consuming or using a product if the anticipated values are less, irrespective of any other factors [52]. Reviewing past literature, little research has been done in the realm of tourism-or other fields of study-regarding the relationship between affordance and perceived value.…”
Section: Perceived Ecotourism Design Affordances and Perceived Value ...mentioning
confidence: 99%
See 1 more Smart Citation